(untitled) (El Taco en la Brea, 2022)
This work studies the sounds in the writing of Juan L. Ortiz. The proposal of a phon/ethic is the hypothesis that guides this study. A specific question is analyzed: the belonging of the poetic voice to what the poet calls «the voice from outside». Suspension of the assertive function of language and continuous questioning will be studied. A specific linguistics will be postulated in the resonance experience of Ortiz´s poetry.